2001
DOI: 10.1046/j.1439-0418.2001.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of host plant resistance in Oryza sativa to the African rice gall midge, Orseolia oryzivora Harris and Gagné (Dipt., Cecidomyiidae), with a description of a new method for screening under artificial infestation

Abstract: A new method is described for screening rice germplasm for resistance to the African rice gall midge (AfRGM), Orseolia oryzivora, year‐round under conditions similar to a severe natural outbreak, using an AfRGM culture to start infestation in a tunnel screenhouse over an irrigated rice field. During 1996 and 1997, 907 test entries of Oryza sativa were screened. Eighteen entries, 17 of which were traditional African lines, had infestation levels at least 50% below those on the partially resistant check variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Consumption of rice, Oryza sativa L. (Poaceae), is growing rapidly in sub-Saharan Africa (WARDA, 2005), with consumption outstripping production in many countries (Williams et al, 2001;Kormawa et al, 2004;Mohapatra, 2006;Omoloye and Vidal, 2007;WARDA, 2008). The rice production deficit in Nigeria is attributed mainly to low rice yields due to insect pest infestation (WARDA, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of rice, Oryza sativa L. (Poaceae), is growing rapidly in sub-Saharan Africa (WARDA, 2005), with consumption outstripping production in many countries (Williams et al, 2001;Kormawa et al, 2004;Mohapatra, 2006;Omoloye and Vidal, 2007;WARDA, 2008). The rice production deficit in Nigeria is attributed mainly to low rice yields due to insect pest infestation (WARDA, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nacro et al. 1996 and Williams et al. 2001 showed that an increase of 1% in the percentage of tillers with galls at stem‐elongation reduced yield by 2–3%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tolerant varieties such as Cisadane experience a lower level of yield loss than more susceptible varieties. Nacro et al 1996 andWilliams et al 2001 showed that an increase of 1% in the percentage of tillers with galls at stem-elongation reduced yield by 2-3%. In addition to reducing grain yield, AfRGM attack also results in delayed and uneven grain maturation, which makes harvesting difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of yield loss caused by the gall midge larva varies among rice varieties. Nacro et al [2], and Williams et al [3] showed that an increase in 1% in the percentage of tillers with galls at the stem-elongation stage reduced yield by 2 to 3%.…”
Section: Introductionmentioning
confidence: 99%